Rehabilitacija bolnikov po možganski kapi - Goljar, Nika (Rehabilitacija (Ljubljana), 2010)
Despite recent advances in understanding of post-stroke rehabilitation, the evidence base remains weaker than in other areas of stroke management. European Stroke Organization (ESO) published (in 2008) its Guidelines for Management of Ischaemic Stroke (updated in 2009). They cover the whole spectrum of ischaemic stroke, including rehabilitation. Following the systematic literature search, the selected articles were screened for data relevance and quality, and the evidence base for post-stroke rehabilitation interventions was appraised. The ESO Guidelines are summarized in this article. Since there is a lack of robust evidence for many of the prevalent post-stroke rehabilitation interventions, specific areas that require further study are highlighted.
Keywords: delovna terapija; fizikalna terapija; možganska kap; rehabilitacija; vocational rehabilitation; zapleti